Kinetics of the fluoride and arsenic adsorption using alumina nanofibers - Zamorategui-Molina, Adrían (Universidad Autónoma de Tamaulipas, 2019)
In many countries of the world including Mexico, the presence of toxic elements such as arsenic and fluoride on the maximum levels permitted in drinking water (0.01 mg/L and 1.5 mg/L) is causing health problems such as cancer and skeletal fluorosis, respectively. For this reason, the objective of this work was to determine the kinetics of adsorption process of the fluoride and arsenic in synthetic water using gamma alumina (γ-Al2O3) and to determine whether the process develops spontaneously. Nanofiber γ-Al2O3 with high surface area was synthesized by homogeneous precipitation and spray dry method. This adsorbent nanomaterial was used to remove fluoride and total arsenic from synthetic water. Nanofiber morphology of the mesoporous γ-Al2O3 was analyzed by transmission and scanning electron microscopy. The high surface area (352 m2/g) was determined by nitrogen adsorption-desorption. The adsorption isotherms of the removal process concur by the Langmuir model for both toxic elements. γ-Al2O3 removes up to 96 % of fluoride ions and 92 % of total arsenic at pH5, while a removal of 90 % and 94.2 % at pH7 of fluoride and arsenic, respectively, is achieved. The removal kinetics follows the pseudo-second order model, and the dimensionless equilibrium parameter and Gibbs standard free energy confirm that the process is performed spontaneously. The gamma nano-fibrillar alumina is a good material for the natural and spontaneous removal of arsenic and fluoride present in synthetic water used in this study.